Why has the Norwegian krone exchange rate been persistently weak? A fully simultaneous VAR approach - Andreas Benedictow; Roger Hammersland (Statistics Norway, Research Department, 2022)
We identify variables that help explain the persistent weakness of the Norwegian krone since 2016 within a fully simultaneous model of the underlying process driving the krone-euro exchange rate. In addition to a set of fundamental variables we consider non-traditional explanatory variables related to an exchange rate premium, inspired by several claims to insights made by market participants. The weak Norwegian krone seems to be largely attributable to factors related to the risk premium, such as the declining importance of petroleum in the Norwegian economy, a relative reduction in FDI in Norway and a fall in oil industry-specic share prices.
Keywords: C22; C32; F31; F41; G15; 330; Exchange rate; Foreign exchange rate premium; Cointegration; VAR-analysis